2022
DOI: 10.14336/ad.2022.0104
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Gut Microbiota Metabolites, Current Status and Future Perspectives

Abstract: Gut microbiota, a collection of microorganisms that live within gastrointestinal tract, provides crucial signaling metabolites for the physiological of hosts. In healthy state, gut microbiota metabolites are helpful for maintaining the basic functions of hosts, whereas disturbed production of these metabolites can lead to numerous diseases such as metabolic diseases, cardiovascular diseases, gastrointestinal diseases, neurodegenerative diseases, and cancer. Although there are many reviews about the specific me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
121
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(123 citation statements)
references
References 210 publications
0
121
0
2
Order By: Relevance
“…When absorbed, gut microbiota metabolites can be transported to target organs and tissues that are remote from gastrointestinal tract, and therefore exert a wide range of activities on hosts. These activities include, but not limited to, regulating the composition and function of gut microbiota, acting as nutrition, influencing nutrition absorption, modulating host metabolism, influencing intestinal barrier and gut motility, impacting the local and systemic immune response, modulating circadian rhythm and nervous system ( 6 ). With these bioactivities, gut microbiota metabolites play important roles in the development and progress of a variety of diseases such as cancer, non-alcoholic fatty liver disease, hypertension, Parkinson's disease, and ulcerative diseases ( 30 , 38 40 ).…”
Section: Gut Microbiota Metabolites In a Nutshellmentioning
confidence: 99%
See 3 more Smart Citations
“…When absorbed, gut microbiota metabolites can be transported to target organs and tissues that are remote from gastrointestinal tract, and therefore exert a wide range of activities on hosts. These activities include, but not limited to, regulating the composition and function of gut microbiota, acting as nutrition, influencing nutrition absorption, modulating host metabolism, influencing intestinal barrier and gut motility, impacting the local and systemic immune response, modulating circadian rhythm and nervous system ( 6 ). With these bioactivities, gut microbiota metabolites play important roles in the development and progress of a variety of diseases such as cancer, non-alcoholic fatty liver disease, hypertension, Parkinson's disease, and ulcerative diseases ( 30 , 38 40 ).…”
Section: Gut Microbiota Metabolites In a Nutshellmentioning
confidence: 99%
“…Gut microbiota can produce gases (H 2 S, H 2 , CO 2 , CH 4 , NO) ( 6 , 35 ). CH 4 has significant effect on gastrointestinal tract as it is associated with constipation and can slow the colon motility ( 149 ).…”
Section: Gut Microbiota Metabolites Modulated By Dietary Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have confirmed that human fecal microflora could transform baicalin to baicalein and oroxylin A, which exhibit a more potent anti-scratching behavioral effect than their parent molecule in histamine-treated mice ( Jung et al, 2012 ; Cheng et al, 2021 ). Moreover, the bioavailability of herbal compounds can be further improved by their possible effect on the production of microbial metabolites ( Zhang et al, 2020 ; Liu et al, 2022 ). Therefore, gut microbiota combined with metabolomics is widely used to study the mechanism of Chinese medicine ( Feng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%